Recepcja mitologii słowiańskiej w literaturze polskiego oświecenia - Karpińska, Monika (Uniwersytet Rzeszowski, 2022)
W dysertacji pt. „Recepcja mitologii słowiańskiej w literaturze polskiego oświecenia” prześledzony został materiał mitologiczny w twórczości przełomu wieków XVIII i XIX z uwzględnieniem przyjętych metodologii badań: narratywizmu, sztuki interpretacji oraz krytyki mitograficznej. Na podstawie tego rozróżnienia dokonano analizy recepcji mitologii słowiańskiej w literaturze polskiego oświecenia. Pod uwagę zostały wzięte teksty z trzech etapów epoki rozumu: czasów saskich, stanisławowskich i porozbiorowych. Rozpowszechniona periodyzacja została jednak nieco rozszerzona ze względu na procesowy charakter omawianego zjawiska. Dokonało się ono na gruncie wielu dziesięcioleci i określane być może mianem słowiańskiego przełomu. Przeprowadzone badania wpisują się w coraz popularniejszy nurt rozważań nad piśmiennictwem wieku świateł akcentujący pozaracjonalne inspiracje. Należy jednak podkreślić, iż obecność wątków mitologii słowiańskiej w literaturze przełomu wieków XVIII i XIX stanowi wynik dociekań antropologicznych oraz naukowej wiedzy o społecznościach przedchrześcijańskich.

The dissertation „Assimilation of Slavic mythology in the literature of Polish Enlightenment” traces the mythological material present in the literature of the turn of 18 th and 19 th century with consideration to chosen research methodology, including: narrativism, the art of interpretation, and mythographic criticism. Taking into account the above distinction, the author conducted the analysis of assimilation of Slavic mythology in the literature of Polish Enlightenment. The texts originating from three periods of the Age of Reason (Saxon period, Stanisław August Poniatowski’s reign, and post-partition period) were analysed. The author decided to extend the applicable chronology slightly further, for the discussed phenomenon, which may be termed “Slavic breakthrough”, had had a progressive nature and had stretched over several decades. Conducted research reflects the growing tendency in studies of Enlightenment literature that emphasises its irrational inspiration. However, it must be underlined that the elements of Slavic mythology present in the literature of the turn of 18 th and 19 th stems from anthropological inquiries and scientific knowledge about pre-Christian communities.
Assimilation of Slavic mythology in the literature of Polish Enlightenment
Promotor: prof. dr hab. Marek Nalepa - 203 s.
Keywords: mitologia słowiańska; Oświecenie; Oświecenie polskie; literatura polska; Slavic mythology; Enlightenment; Polish Enlightenment; Polish literature